PERBANDINGAN DAYA BIOLARVASIDA EKSTRAK BIJI BUAH DAN DAUN PEPAYA (Carica papaya) TERHADAP LARVA Aedes aegypti - Fidel Corona; Freggy Spicano Joprang (Atma Jaya Catholic University of Indonesia, 2019)
Introduction: Aedes aegypti is the major vector of dengue virus. Dengue virus can cause dengue hemorrhagic fever (DHF). DHF is dangerous because it can cause death. World Health Organization (WHO) noted Indonesia as state with the highest dengue cases in Southeast Asia. Effort to control A. aegypti vector that can be done is by using natural substances that have the effect of biolarvicides. This study aims to determine natural biolarvicides potencial of fruit seeds and leaf papaya (Carica papaya) extracts against A. aegypti larvae. Methods: This study was an experimental study and conducted in 2016 using two groups of samples with the design before and after intervention. Samples were A. aegypti larval instar III and IV with the number of 10 larvaeper concentration and 10 larvae of control for each types of extracts. The concentration used was 0 mg / L (control), 50 mg / L, 100 mg / L, and 150 mg / L for both types of extracts, then observed at 6 hours, 12 hours, 18 hours, and 24 hours after exposure. Results: This study using Kruskal Wallis test, p value = 0.352. (P> 0.05) means there is no significant difference in the effect of biolarvicides concentration between the two types of extracts that used to the number of dead larvae of A. aegypti. Conclusion: Fruit seeds and leaf papaya extracts (C. Papaya L.) with concentrations of 50 mg / L, 100 mg/ L, and 150 mg / L are not effective to kill the larvae of A. aegypti. Other studies show concentrations above 21.9 ppm of leaf extract and 442 ppm of fruit seed extract can effectively kill larvae, therefore future studies are needed to determine effective extract concentrations to kill the larvae of A. aegypti.